Bioactive Products From Plant-Endophytic Gram-Positive Bacteria - Ek-Ramos, María J.; Gomez-Flores, Ricardo; Orozco-Flores, Alonso A.; Rodríguez-Padilla, Cristina; González-Ochoa, Guadalupe; Tamez-Guerra, Patricia (Frontiers in Microbiology, 2019)
Endophytes are mainly bacteria or fungi living within plants showing more beneficial than adverse effects in the host. Endophytes are found in most ecosystems; they help to reduce plant crops’ biotic and abiotic stressors by stimulating the immune response, excluding plant pathogens by niche competition, and participating in antioxidant activities and phenylpropanoid metabolism, whose activation produces metabolites related to plant defense, structural support, and survival. In fact, metabolomic studies have demonstrated that endophyte genes associated to specific metabolites are involved in plant growth promotion (PGP) by stimulating plant hormones production such as auxins and gibberellins or as plant protective agents against microbial pathogens, cancer, and insect pests, but eco-friendly and eco-safe. Among agriculture, forest, mangrove, and medicinal plants, a number of Gram positive endophyte metabolites, mainly from the Firmicutes phyla, have demonstrated to have distinctive biocontrol and plant growth‐promoting activities. In general, Actinobacteria and Bacillus endophytes produce aromatic compounds, lipopeptides, plant hormones, polysaccharides, and several enzymes linked to phenylpropanoid metabolism, thus representing high potential for PGP and crop management strategies. Indeed, Actinobacteria are linked to antimicrobial- and antitumor-like activity metabolites production, useful in agriculture, medical and veterinary application. The great endophytes diversity, their metabolites production, and their adaptation to stress conditions make them a suitable and unlimited source of novel metabolites, whose application could reduce agrochemicals usage in food and drugs production.